Effect of swift heavy ion (SHI) irradiation on the structural and optical properties of N implanted CVT grown ZnSe single crystals. (August 2015) - Kannappan, P.; Baskar, K.; Krishna, J.B.M.; Asokan, K.; Dong, C.L.; Chen, C.L.; Lu, Y.R.; Dhanasekaran, R.
Abstract: Present study reports the variation of structural and optical properties of N implanted ZnSe single crystals grown by a Chemical Vapor Transport (CVT) technique due to120 MeV Au ion irradiation. The grazing incidence X-ray diffraction (GIXRD) results show that the full width at half maximum (FWHM) increases on irradiation. The surface morphology of irradiated sample shows the pits and islands by AFM studies. The optical absorption cut off wavelength is 493 nm for as grown ZnSe whereas for the implanted and irradiated samples cut off wavelength shift towards red region. The photoluminescence spectrum shows the emission wavelength is at 592 nm whereas for the implanted-irradiated samples PL emission shift towards red region. The intensity of defect level emission decreases due to Au irradiation. The FT-Raman spectrum shows the peak at 252 cm −1 due to LO mode of Zn–Se lattice vibrations. The X-ray absorption near edge structure (XANES) study was performed for the as grown and irradiated samples. The detailed investigation on the structural and optical properties of the N implanted and Au irradiated ZnSe single crystal was carried out.